Orientasi Kewirausahaan Dan Network Capability Sebagai Upaya Pencapaian Kinerja Perusahaan Di Masa Pandemi Covid-19 - Laila Hamidah; R. Deni Muhammad Danial; Nor Norisanti (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The company performance means the company's ability to achieve its financial and non-financial goals with the use of its resources to be able to compete. This study was held at small and medium enterprise restaurants in Sukabumi city to be able to achieve company performance in the COVID-19 pandemic era. The aim of this study were to find out and interpreting the role or the influence of entrepreneurial orientation and network capability toward the company performance in small and medium enterprise restaurants. In realizing the achievement of the company's performance, it is necessary for the company to implement strategic steps to stay prominent in the uncertain market conditions because of the COVID-19 virus outbreak continues to make business activities very limited. The implementation method in processing the data in this study was used associative method with quantitative approach. The number of respondents were 37 who is a business owner or manager in a restaurant business in Sukabumi city. Software IBM SPSS Statistics Version 26 was used to record the research results. The findings showed that entrepreneurial orientation and network capability had a positive and significant effect also had a very strong correlation value of 0.859. Therefore, can be concluded that entrepreneurial orientation and network capability have influence in achieving company performance by developing renewable ideas and fostering partnerships to help the company's performance succeed. Keywords: Entrepreneurial Orientation, Network Capability, Company Performance